PERENCANAAN KOMUNIKASI PEMERINTAH KOTA PAYAKUMBUH DALAM MEMPERTAHANKAN KOTA SEHATYANG BERKELANJUTAN - Aprilla, Monica; ", Yasir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Environmental pollution caused by natural disasters and also human activities, resulting in the decline in environmental quality both in the city and in the village. Environmental pollution that occurs can not be burdened on one side only, but there must be collaboration between society and also government. One of Payakumbuh government's efforts in dealing with pollution that occurred in Payakumbuh City, namely by creating a healthy city program called Payakumbuh Sustainable Healthy City. This study aims to determine the process of communication planning in making Payakumbuh Healthy City program.This research uses descriptive qualitative research type by using Assifi and French communication planning model. The subjects of the study consisted of four persons involved in the making of selected programs using purposive techniques. This study uses data collection techniques through in-depth interviews, observation, and documentation. To achieve the validity of data in this study, the authors use triangulation.The results showed that first, the targeted audience in this healthy city program is the whole Payakumbuh community that is in the process of building a clean attitude. Second, the message delivered in this healthy city program is a message that is informative and also persuasive where the message invites the public to keep the cleanliness of the city. Third, the media used in the dissemination of the message is by way of communication in interpersonal, group communication and also media communication. Fourth, evaluation is done by determining the monitoring point to be evaluated, view the field condition, see the program implementation. After that, the government summoned the OPD through the Mayor as the person in charge, then the Mayor will define the deficiency to OPD and OPD here who will be tasked to meet the deficiencies that occurred in the field.Key Word: Planning, Communication, Government